Effect of thrombectomy on oedema progression and clinical outcome in patients with a poor collateral profile. Issue 2 (18th November 2020) - Broocks, Gabriel; Kemmling, Andre; Faizy, Tobias; McDonough, Rosalie; Van Horn, Noel; Bechstein, Matthias; Meyer, Lukas; Schön, Gerhard; Nawabi, Jawed; Fiehler, Jens; Kniep, Helge; Hanning, Uta
Abstract : Background and purpose: The impact of the cerebral collateral circulation on lesion progression and clinical outcome in ischaemic stroke is well established. Moreover, collateral status modifies the effect of endovascular treatment and was therefore used to select patients for therapy in prior trials. The purpose of this study was to quantify the effect of vessel recanalisation on lesion pathophysiology and clinical outcome in patients with a poor collateral profile. Materials and methods: 129 patients who had an ischaemic stroke with large vessel occlusion in the anterior circulation and a collateral score (CS) of 0–2 were included. Collateral profile was defined using an established 5-point scoring system in CT angiography. Lesion progression was determined using quantitative lesion water uptake measurements on admission and follow-up CT (FCT), and clinical outcome was assessed using modified Rankin Scale (mRS) scores after 90 days. Results: Oedema formation in FCT was significantly lower in patients with vessel recanalisation compared with patients with persistent vessel occlusion (mean 19.5%, 95% CI: 17% to 22% vs mean 27%, 95% CI: 25% to 29%; p<0.0001). In a multivariable linear regression analysis, vessel recanalisation was significantly associated with oedema formation in FCT (ß=−7.31, SD=0.015, p<0.0001), adjusted for CS, age and Alberta Stroke Program Early CT Score (ASPECTS). Functional outcome was significantly better in patients following successful recanalisation (mRS at day 90: 4.5, IQR: 2–6 vs 5, IQR: 5–6, p<0.001). Conclusion: Although poor collaterals are known to be associated with poor outcome, endovascular recanalisation was still associated with significant oedema reduction and comparably better outcome in this patient group. Patients with poor collaterals should not generally be excluded from thrombectomy.